Substantiation of effectiveness of trainings on health related methodic for students with weakened motor fitness - V.A. Kuzmin; Yu.A. Kopylov; M.D. Kudryavtsev; G.Y. Galimov; S. S. Iermakov (Physical Education of Students)
Purpose: to work out methodic, facilitating successful conduct of health related trainings of students withy weakened motor (physical) fitness. Material: in the research 47 students with weakened motor fitness participated. Analysis of indicators of morbidity frequency and duration was carried out on the base of medical records’ studying during all academic year. Experimental methodic consisted of three chapters: execution of specifically selected Hatha yoga static postures, breathing exercises and boxing techniques. Breathing exercises were grouped in four complexes. Every complex was fulfilled during 6 trainings, after each of them the next followed. Results: it was found that frequency and duration of diseases statistically confidently decreased in academic year. It was shown that formation of healthy life style skills statistically confidently improved. Conclusions: we have determined: increased students’ interest to physical culture practicing; reduction of frequency and duration of diseases; higher level of formation of healthy life style skills.